Downregulation of the endogenous opioid peptides in the dorsal striatum of human alcoholics - Sarkisyan, Daniil; Hussain, Muhammad Z.; Watanabe, Hiroyuki; Kononenko, Olga; Bazov, Igor; Zhou, Xingwu; Yamskova, Olga; Krishtal, Oleg; Karpyak, Victor M.; Yakovleva, Tatiana; Bakalkin, Georgy (Frontiers in Cellular Neuroscience, 2015)
The endogenous opioid peptides dynorphins and enkephalins may be involved in brain-area specific synaptic adaptations relevant for different stages of an addiction cycle. We compared the levels of prodynorphin (PDYN) and proenkephalin (PENK) mRNAs (by qRT-PCR), and dynorphins and enkephalins (by radioimmunoassay) in the caudate nucleus and putamen between alcoholics and control subjects. We also evaluated whether PDYN promoter variant rs1997794 associated with alcoholism affects PDYN expression. Postmortem specimens obtained from 24 alcoholics and 26 controls were included in final statistical analysis. PDYN mRNA and Met-enkephalin-Arg-Phe, a marker of PENK were downregulated in the caudate of alcoholics, while PDYN mRNA and Leu-enkephalin-Arg, a marker of PDYN were decreased in the putamen of alcoholics carrying high risk rs1997794 C allele. Downregulation of opioid peptides in the dorsal striatum may contribute to development of alcoholism including changes in goal directed behavior and formation of a compulsive habit in alcoholics.